The Relationship Between Vitamin D Levels and the Severity of Anxiety and Depression in Patients Under Methadone Maintenance Treatment - Abdolahzade-Arani, Fateme; Kahrizi, Farzad; Ghaderi, Amir; Banafsheh, Hamid Reza (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Hypovitaminosis D, low bone mineral density, non-specific musculoskeletal pain, increased risk of fracture, and periodontal disease were reported in most subjects recruited from the Methadone Maintenance Treatment (MMT) program. This study aimed to determine the relationship between vitamin D levels and the severity of anxiety and depression in patients under MMT. Methods: In a cross-sectional study, serum vitamin D levels were measured among 500 patients under MMT from Kashan Province, Iran. Correlation tests were used to assess the association of vitamin D levels with the severity of anxiety and depression in the explored patients. Results: We found that serum vitamin D levels were positively correlated with the scores of the Beck Depression Inventory (BDI) (r=0.107, P=0.017) and the Beck Anxiety Inventory (BAI) (r=0.129, P=0.004). Additionally, there was a negative correlation between serum vitamin D levels, MMT dosage (r=-0.011, P=0.8), and the duration of MMT (r=-0.017, P=0.7). Conclusion: Our findings demonstrated that serum vitamin D levels were independently correlated with the BDI and BAI scores. Further studies are required to confirm our findings.